Potential of Some Natural Media as Alternative Media for Growth of Bacillus sp. - Kusumawati, Diah Budi; Wuryandari, Yenny; Purnawati, Arika (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: Bacillus sp. as a biological agent can be an environmentally friendly disease control solution by producing antimicrobial compounds. However, expensive culture media is an obstacle in its use. Alternative media made from natural materials such as legumes are considered potential because they are rich in nutrients and affordable. This study aims to find the best alternative media that support the growth and viability of Bacillus sp. isolate Bcz 30. Method: This research was conducted at the Plant Health Laboratory of the National Development University “Veteran” East Java in July-November 2024. This research used a completely randomized design (RAL) with one stage of in vitro testing. The implementation of the test stages includes testing the growth of Bacillus sp. isolate Bcz 30 on each alternative media, testing the viability of Bacillus sp. isolate Bcz 30 on liquid media then the two highest viability results on liquid media will be continued for viability tests on different formulations, namely solid and liquid formulas. Analysis of the data obtained using the variance analysis test (ANOVA), if the data presented is significantly different, it will be continued with the BNJ test at the 5% level. Result: Based on the growth test, tolo bean and lamtoro gung media can replace NA media. Based on the liquid formula viability test, tolo bean and lamtoro gung media with 30% concentration had the highest viability results. Based on the formulation test, the solid formula can maintain the viability of Bacillus sp. than the liquid formula. Conclusion: Bean and lamtoro gung media with 30% concentration formulated with solid formula is the best alternative media for Bacillus sp. isolate Bcz 30.